ئامانج و جۆرەكانى گەشەپێدان شيكردنەوەيەكى تيۆرى بەشێك لەنامەى ماستەر بەناونيشانى(گەنج و گەشەپێدانى كلتورى/ دەرفەت و ئاڵەنگارييەكان) توێژينەوەيەكى سۆسيۆلۆجيە لەشارى سلێمانى - حسێن, توانا فەرەيدون; عزيز, سەركەوت عبدالقادر (Sulaimani Journal for Humanities, 2022)
Development is a deep organized and professional process that reads the possibilities to change the society positively. It tries to take the society from steadfast situation to turning and developing point. It aims to make development in all the fields by taking benefit from human and financial resources and the new ideas that appear. The development types are aiming at interfering the government works in a systematic way to reach development point and raise the living quality level and welfare. On the other hand, the aims of development are regarded as attempts for meeting the needs. This is the symbol of a modern and organized society taking steps to raise the life quality. This is a manifestation of the modernity of society that is moving towards progress and rising capacities and competencies as well as improving the quality of life and well-being.